Workplace health promotion in a continuous Rationalised Hospital sector - Thor Christian Bjørnstad (SSM: Qualitative Research in Health)
The article explores the complexities of implementing health-promoting physical activity within the context of a Norwegian public hospital. Through an extensive case study, it examines the rollout of Active Hospitals, a program crafted in alignment with prevailing best practices in workplace physical activity. Departing from prior studies, the article adopts the perspective of the implementation facilitators. It illustrates how the implementation process faced obstacles stemming from new organizational paradigms, characterized by heightened rationalization, standardization, and perpetual restructuring within the sector. Consequently, the article underscores how reforms associated with New Public Management significantly limits health policies' ambitions to turn the workplace into a health-promoting setting These challenges are particularly pertinent concerning the enduring goals of social sustainability.